SPEECH ACT AND TRANSITIVITY IN ANNUAL PRESS STATEMENT SPEECH 2017 BY MINISTER OF FOREIGN AFFAIRS OF THE REPUBLIC OF INDONESIA - AINI, MASHITA (LANGUAGE HORIZON, 2018)
This research focuses on the analysis of speech act and transitivity emerge in Annual Press Statement Speech 2017 by Minister Foreign Affairs. The purpose of this research is to reveal the significance of speech act and transitivity emerged through Annual Press Statement speech. This research includes the analysis of each types of speech act and transitivity process in the speech by employing theory of Speech Act by Yule combined with Transitivity process theory proposed by Halliday. It is combined with illocutionary act and Halliday?s SFL theory to analyze the function implicitly emerged throughout the speech. Since the data of this research are the Minister utterances in script of Annual Press Statement speech, this research employed descriptive qualitative approach and documentary study. The results show that all of the types of speech act are found in the speech. Those are; Representatives, Declaratives, Expressives, Directives and Commissives. Representatives are the most frequently used type in the speech it is used to convey factual information and description regarding with diplomacy performances. Meanwhile among six types of transitivity process, there are only three types that are found from the Minister utterance in the speech, those are; Material Process, Mental Process, and Relational Process. Since those processes are three main processes in English Transitivity approach. Material process is the most frequently used process since it described tangible action in diplomacy context such as performances and accomplishments of Indonesia diplomacy. Through Material Process, the Minister conveyed act and performance which is accomplished by the Minister and staffs. The Minister also used Mental process to share her feeling and perception toward challenge encountered in managing diplomacy affairs. While the Minister used Relational process to describe the identifying of Indonesia by stating Indonesia?s contribution and cooperation for diplomacy. Based on the analysis in revealing the function of Speech act and Transitivity emerged through the Annual Press Statement speech, this research is analysed by employing theory of illocutionary of speech act combined with transitivity and Halliday?s SFL theories. There are four major functions of speech act and transitivity produced in the speech which is identified from different process of transitivity and types of speech act. Material process followed by representatives type of speech act produce the function for empowering the audiences by describing the performance, accomplishment and achievement through the speech. The statement contained Material process followed by Directives type created the function for motivating the audience in the form of suggestion to the audience in order to improve their work and performance for diplomacy interest. By applying Representatives and Relational process, it is used to show Indonesia?s integrity in managing diplomacy by describing Indonesia?s involvement and contribution in several associations. The Minister tried to influence the audience in order to increasing their commitment through mental process and expressive type by stating appreciation words for the whole performance and hard work in handling diplomacy concern.